The Role of Indonesian Students in the Maulid Festival: An Effort to Introduce English Culture and Education in Thailand - RAHMAH, Ridha putri aulia; ROHIM, Abdul; NARGIS, Nargis (Indonesia Strategic Sustainability, 2025)
The International Community Service Program (Kuliah Kerja Nyata - KKN) is a form of community engagement that allows students to contribute to education and cultural exchange in their host country. This article discusses the role of Indonesian students in the Maulid Festival in Thailand and their efforts to introduce Islamic Nusantara culture and the importance of English education to the local community. The Maulid Festival serves as a platform for students to showcase Indonesian traditions in celebrating the Prophet Muhammad’s birthday through various activities, such as cultural performances, religious lectures, and traditional cuisine. Additionally, students conduct socialization programs emphasizing the significance of English as a global skill that can expand educational and economic opportunities for the Thai community. Through this initiative, students not only act as cultural ambassadors but also as agents of change in raising awareness of the importance of learning foreign languages. This program demonstrates that the integration of culture and education can be an effective approach to community service while strengthening bilateral relations between Indonesia and Thailand.